TEACHER COMPETENCIES GROUNDED IN THE VALUES OF QUR'AN SURAH ALI IMRAN (3):159 FOR FOSTERING HUMANISTIC AND PARTICIPATORY PEDAGOGY IN THE ERA OF ARTIFICIAL INTELLIGENCE - Muhammad Burhan Ashfiya' (IAIN Bone, 2026)
The rapid advancement of Artificial Intelligence (AI) in education has improved instructional effectiveness but also raised concerns about the declining humanistic dimension of teaching. This study aims to analyze teacher competencies in light of the values of the Qur'an, Surah Ali Imran, Verse 159, and to formulate a humanistic-participatory pedagogical framework for the AI era. Using a qualitative conceptual approach, the study examines contemporary Qur’anic interpretations and relevant literature on teacher competence, humanistic pedagogy, and Islamic education. The findings show that the values of compassion, consultation, forgiveness, and reliance on God are embedded in QS. Ali Imran Verse 159 provides an integrative foundation for teacher competencies that extend beyond technical and instructional aspects. The analysis further indicates that contemporary educational discourse largely emphasizes pedagogical effectiveness and technological adaptation, while ethical and spiritual dimensions receive limited attention. Based on the synthesis of Qur’anic interpretation and educational literature, this study proposes a humanistic-participatory pedagogical framework that positions teachers as facilitators, moral role models, and dialogic partners in learning. The study contributes theoretically by enriching the value-based paradigm of teacher competence from an Islamic perspective and practically by offering a conceptual reference for developing inclusive, dialogic, and character-oriented learning in the AI era. These findings underscore the importance of integrating Qur’anic values into contemporary educational transformation to foster a more holistic and sustainable learning paradigm.